Airport Dominance and Airline Pricing Power: An Investigation of Hub Premiums in the Chinese Domestic Market - Chen, Ruowei (Cranfield University, 2013)
Concerns on market power conferred by airport dominance and the debates of hub premiums have attracted longstanding attention from governments and academics alike. Most previous studies mainly focus on the fully deregulated markets such as the United States and Europe, what remains unknown is how such effects change when a country evolves from a tightly controlled regime to a deregulated market. This research analyses the effects of airport dominance on airline pricing power with the empirical study based on the Chinese domestic market using fixed- effect panel data models. Results from the regression analysis indicate that airport dominance is the most important source of pricing power in the gradually deregulated Chinese domestic market. Hub carriers are able to charge higher prices to premium class passengers and non-hub carriers can benefit from the “umbrella effects” of hub premiums. However, hub carriers are not able to translate their airport dominance to pricing power in the economy class market, whereas non-hub carriers even have to reduce the prices as their market shares at major airports increase. This study contributes to the literature by explicitly segmenting the market into economy and premium classes. The results have important policy implications.
Keywords: Airport Dominance; Airfares; Market Power; Hub Premiums; Chinese Domestic Market